Environmental toxicology wars: Organ-on-a-chip for assessing the toxicity of environmental pollutants. (1st January 2021) - Yang, Sheng; Chen, Zaozao; Cheng, Yanping; Liu, Tong; Lihong Yin,; Pu, Yuepu; Liang, Geyu
Abstract: Environmental pollution is a widespread problem, which has seriously threatened human health and led to an increase of human diseases. Therefore, it is critical to evaluate environmental pollutants quickly and efficiently. Because of obvious inter-species differences between animals and humans, and lack of physiologically-relevant microenvironment, animal models and in vitro two-dimensional (2D) models can not accurately describe toxicological effects and predicting actual in vivo responses. To make up the limitations of conventional environmental toxicology screening, organ-on-a-chip (OOC) systems are increasingly developing. OOC systems can provide a well-organized architecture with comparable to the complex microenvironment in vivo and generate realistic responses to environmental pollutants. The feasibility, adjustability and reliability of OCC systems make it possible to offer new opportunities for environmental pollutants screening, which can study their metabolism, collective response, and fate in vivo. Further progress can address the challenges to make OCC systems better investigate and evaluate environmental pollutants with high predictive power. Graphical abstract: Image 1 Highlights: Common environmental pollutants and related adverse health effects are elaborated. Limitations of conventional environmental toxicology screening cannot predict actual human toxicity responses. Organ-on-a-chip can assess toxicity of environmental pollutants more accurately. Human-on-a-chip will be the best platform for environmental toxicology studies in the future.